2014
DOI: 10.1037/a0032623
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and mental health outcomes in Mexican TBI caregivers.

Abstract: Research has documented the deleterious effects on caregivers of providing care for an individual with traumatic brain injury (TBI). TBI caregivers in Mexico specifically have reduced health-related quality of life (HRQOL) across both physical and mental health domains. The purpose of the current study was to uncover the system of connections between Mexican TBI caregivers' HRQOL and their mental health. A cross-sectional survey was conducted at a public medical facility in Guadalajara, México. Ninety family c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…Studies have demonstrated that depression negatively affects HRQL in individuals with TBI [ 42 , 55 , 56 ]. Additionally, in caregivers, improvements in HRQL have been associated with improvements in symptoms of depression and anxiety [ 57 ], and strong correlations between depression and HRQL have been identified [ 58 ]. Although much of this research refers to patients and caregivers facing moderate to severe TBI, parallel associations were found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that depression negatively affects HRQL in individuals with TBI [ 42 , 55 , 56 ]. Additionally, in caregivers, improvements in HRQL have been associated with improvements in symptoms of depression and anxiety [ 57 ], and strong correlations between depression and HRQL have been identified [ 58 ]. Although much of this research refers to patients and caregivers facing moderate to severe TBI, parallel associations were found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument has demonstrated adequate internal consistency, with Cronbach's alphas generally above 0.85 [ 44 ]. The SF-36 has been used extensively in Latin America with previous research on caregivers of individuals with neurological conditions such as multiple sclerosis [ 45 ], traumatic brain injury [ 46 ], and dementia [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous examinations of those providing care to individuals with traumatic brain injury (TBI) found that they frequently feel overwhelmed [6,7]. Low health-related quality of life among TBI caregivers has been associated with decreased mental health status [8]. Caregivers of individuals with spinal cord injury (SCI) can experience depressive symptoms at similar rates as the injured person [9], whereas caregivers of individuals with burn injuries experience more pronounced symptoms of depression than caregivers of individuals who are hospitalized for other reasons [10].…”
Section: Introductionmentioning
confidence: 99%